Medical Audit of Hemophilia Services for National Health Insurance Participants in Bogor: A Case Report - Pharadiba, Marselly; Taufiq, Wildan Zayyin; Sambas, Jenal M.; Nampira, Rizal Ashari (Jurnal Jaminan Kesehatan Nasional, 2024)
BPJS Kesehatan is a legal entity established to implement social security programs, provide health service benefits through regulations, and manage (purchasing and investing) carefully, prudently, transparently, efficiently, and effectively.  One of the health service benefits provided by BPJS Kesehatan is for hemophilia. Hemophilia is a hereditary blood clotting disorder that is currently the most prevalent globally and is based on X-linked recessive genetic inheritance. Since the Regulation of the Minister of Health of the Republic of Indonesia Number 3 Year 2023, claims for hemophilia services, including the top-up of anti-hemophilia factor drugs in 2023, have increased. The method used to write this article is quantitative descriptive with a case report approach in the form of a report from BPJS Kesehatan, which conducted an administrative claim audit on the potential fraud committed in an attempt to inflate costs, which is then followed by a medical audit. The result of the medical audit indicated that there were inaccuracies in the financing of hemophilia services based on medical service standards that were not yet met, leading to sanctions that the hospital must undergo, namely the recovery of financing losses.